1984
DOI: 10.1161/01.res.55.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Altered cerebral vessel innervation in the spontaneously hypertensive rat.

Abstract: SUMMARY. Autonomic innervation in the cerebral arterial walls of adult male spontaneously hypertensive rats and of normotensive Wistar-Kyoto rats was studied. When examined by fluorescence microscopy, dense catecholamine fluorescence was observed in anterior cerebral and middle cerebral arteries of both Wistar-Kyoto and spontaneously hypertensive rats. However, vertebral and basilar arteries and small pial arteries of Wistar-Kyoto rats received extremely sparse or no catecholamine fluorescence, whereas, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
(76 reference statements)
4
23
0
Order By: Relevance
“…Catecholamine fluorescence histochemis try has demonstrated that the major cerebral (extraparenchymal) arteries in mammals, in cluding man and a variety of laboratory ani mals, are innervated by noradrenergic nerves [Nelson and Rennels, 1970;Edvinsson et al, 1972;Owman et al, 1974], The present study has shown that in the gerbil, the ante rior cerebral circulation (internal carotid sys tem) receives a denser noradrenergic inner vation than the posterior circulation (vertebro-basilar system), and this has also been reported in other species [Nielsen and Ow man, 1967;Peerless and Yasargil, 1971;Ed vinsson et al, 1976;Kobayashi et al, 1981;Lee and Saito. 1984], A fluorescence histochemical study was undertaken in order to investigate the distri bution.…”
supporting
confidence: 75%
“…Catecholamine fluorescence histochemis try has demonstrated that the major cerebral (extraparenchymal) arteries in mammals, in cluding man and a variety of laboratory ani mals, are innervated by noradrenergic nerves [Nelson and Rennels, 1970;Edvinsson et al, 1972;Owman et al, 1974], The present study has shown that in the gerbil, the ante rior cerebral circulation (internal carotid sys tem) receives a denser noradrenergic inner vation than the posterior circulation (vertebro-basilar system), and this has also been reported in other species [Nielsen and Ow man, 1967;Peerless and Yasargil, 1971;Ed vinsson et al, 1976;Kobayashi et al, 1981;Lee and Saito. 1984], A fluorescence histochemical study was undertaken in order to investigate the distri bution.…”
supporting
confidence: 75%
“…The cerebral 11 and noncerebral 12 vascular beds of SRSHR have greater densities of sympathetic nerves than those of Wistar-Kyoto normotensive rats. A quantitative increase in sympathetic innervation could protect the cerebrovasculature of SRSHR from hemorrhage during hypertension by either trophically influencing the vasculature to develop a thickened vascular wall.…”
Section: Discussionmentioning
confidence: 80%
“…Ichijma [1969] increased area of NA fluorescent fibres in jejunal arteries from SHR (40-60 days and 4-6 months of age) Berkowitz and Spector [1976] increased NA content (chemical assay) in mesenteric arteries from SHR (10, 15 and 27 weeks of age) Head and Berkowitz [1979] increased NA content (radioenzymatic assay) in mesenteric and renal arteries from SHR (adult) Berkowitz et al [1980] increased NA content (radioenzymatic assay) in mesenteric arteries from SHR (5 and 16 weeks of age) Scott and Pang [1983] increased area of NA fluorescence in jejunal arteries from SHR (2, 4 and 12 weeks of age) Lee and Saito [1984] increased NA fluorescence, increased NA content (radioenzymatic assay) and increased granular vesicle-containing nerves in cerebral blood vessels from SHR (24 weeks of age) Lee et al [1983] increased nerve density in mesenteric arteriolar vessels from SHR (10-12 weeks of age) Head et al [1984] increased NA content (high performance liquid chromatography in conjunction with electrochemical detection HPLC-ECD) in mesenteric arteries from SHR (16-20 weeks of age) Featherston et al [1984] increased density of fluorescent fibres in superior mesenteric arteries from SHR (10 days, 3 weeks and 6 weeks of age) Head et al [1985] increased NA content (radioenzymatic and HPLC-ECD assay) in the mesenteric artery, abdominal aorta, inferior vena cava, kidney and vas deferentia from SHR (16-20 weeks of age) Lee[1985] increased nerve density (morphometric analysis) in large mesenteric arteries from the SHR (3-4 weeks of age) Cassis et al [1985] increased NA fluorescence, increased NA content (HPLC-ECD) and increased number of axon bundles in the caudal artery of the SHR (16 weeks of age) Shimamura et al [1987] increased NA content (HPLC-ECD) in mesenteric arteries from SHRSP and M-SHRSP rats (6 weeks of age) Donohue et al [1988] increased NA content (HPLC-ECD and radioenzymatic assay) in caudal and mes enteric arteries of the SHR (2 days to 17 weeks of age) Albert [1987] increased axonal volume, density of axons and varicositic vesicles in caudal arter ies of the SHR (adult animals) SHR is greater than that of WKY rats from birth [Gray, 1984], It should be cautioned, however, that the early appearance of hypemoradrenergic in nervation is not a characteristic of all blood vessels in the SHR. Donohue et al [1988] have provided evidence which shows that the onset of increased NA contents in the caudal artery of the SHR occurs during the time course of expression of hypertension.…”
Section: Innervation Of Cardiac and Vascular Tissue In The Shrmentioning
confidence: 99%